Metode Latihan Kegiatan Ekstrakurikuler Drum Band Untuk Musik Upacara di SMP Negeri 20 Padang - Agusto, Tio; Yensharti (Universitas Negeri Padang, 2024)
This study aims to describe how the process of training methods for extracurricular drum band activities for ceremonial music at SMP Negeri 20 Padang. This type of research is qualitative research that uses descriptive methods. This research instrument is the researcher himself and is assisted by other supporting instruments such as stationery, digital cameras and tape recoders. Data collection techniques in this study are observation, interviews, documentation and literature studies. Data analysis techniques are carried out by reducing data, presenting data, analyzing data and drawing conclusions. From the results of the study, it was found that there were several methods used by trainers in training extracurricular drum band activities at SMP Negeri 20 Padang. These methods are lecture methods, demonstration methods, individual exercise methods, group exercise methods, and combined exercise methods. Drum Band extracurricular activities are held 2 times a week on Monday and Saturday. The drum band coach of SMP Negeri 20 Padang was appointed by a cultural arts teacher school with a background in fine arts. Even though he has no background in musical art, the coach tries to learn the playing of the Drum Band through videos from youtobe. Drum Band extracurricular activities at SMP Negeri 20 Padang are carried out to develop students' talents but are also aimed at supporting flag ceremony music activities on every monday.